Synthesis and Antitumor Activity of 1,2,4-Triazolo[1,5-a]quinazolines - Al-Salahi, R.; Marzouk, M.; Ashour, A.E.; Alswaidan, I. (Asian Journal of Chemistry, 2014)
Cytotoxicity of 22 triazoloquinazoline compounds was evaluated in vitro against medulloblastoma (Daoy), hepatocellular carcinoma (HepG2) and melanoma (SK-MEL28) cell lines. This study showed that compounds 17, 18 and 21 exhibited remarkable in vitro cytotoxicity against all tested cell lines. Moreover, it was found that compounds 10, 17, 6, 18, 21, 7 and 19 are active against Daoy cell line with IC50 values of 1.29, 2.93, 5.53, 6.14, 6.59, 9.71 and 19 μg/mL, respectively, as compared to that of the reference drug dasatinib (7.26 μg/mL). The HepG2 cell line was affected by compounds 17, 6, 21, 19 and 18 with IC50 values of 4.52, 11.33, 14.69, 16.96 and 24.49 μg/mL, respectively, relative to that of dasatinib (8.21 μg/mL). In addition, compounds 17, 18 and 21 have shown significant antiproliferative activity against SK-MEL28 with IC50 values of 3.88, 13.85 and 14.96, respectively, relative to an IC50 value of 23.83 μg/mL of the reference drug. It is worth mentioning that compounds 6, 10, 17, 18 and 21 are more potent than the reference drug against Daoy cell. In the same manner, 17, 18 and 21 revealed higher cytotoxicity than dasatinib against SK-MEL28 cells. Notably, compound 17 was also more potent than the reference drug against HepG2 cells. In the term of selectivity, compound 10 was found to possess the highest selectivity, as it was active only against Daoy cells. These compounds could be useful as templates for further development through their structural modification to design more potent antitumor agents.